P-564 Advanced paternal age is associated with higher rate of segmental chromosomal aberrations in preimplantation embryos. (30th June 2022) - Abramov, R; Antes, R; Madjunkov, M; Dviri, M; Chen, S; Wilkinson, M; Librach, C; Madjunkova, S
Abstract: Study question: Is there a correlation between paternal age and the frequency of chromosomal aberrations in embryos created by in vitro fertilization (IVF)? Summary answer: There is an association between paternal age and segmental aberration rates in embryos derived from young oocyte providers after adjusting for age, sperm, and IVF-cycle characteristics. What is known already: Paternal reproductive aging(APA) is less understood than maternal reproductive aging(AMA). Embryo aneuploidy presents one of the most important determinants of transfer cycle success. The association of AMA with increased rate of aneuploidy is well established. The systematic review and meta-analysis published by our group did not identify an association of APA with aneuploidy, based on ∼10, 000 pooled embryos, however, the power to detect subchromosomal aberrations was limited by the sensitivity of the PGT-A platform used by each center. Our aim was to study the impact of APA on chromosomal aberrations in a large sample size analyzed by high resolution PGT-A. Study design, size, duration: This was a retrospective cohort study performed at the CReATe Fertility Centre Genetics Laboratory, Toronto, Canada, between January 2019-December 2021. A total of 17731 blastocysts from 3506 cycles (2502 patients) were analyzed using high resolution NGS PGT-A (10Mb resolution; 30%-70% reported as mosaicism). Clinical, laboratory and demographic data were obtained for statistical analysis. Participants/materials, setting, methods: Embryos were allocated into two groups by oocyte-provider age: ≤33years and ≥34years. Each group was divided into four sub-groups by paternal age: Group A 20-29(n = 484); GroupB 30-39(n = 9704); GroupC 40-49(n = 6341); GroupD≥50(n = 1202). Multiple logistic/ordinal regressions were conducted to evaluate euploidy, mosaicism and aneuploidy rates between age groups, as appropriate. Each was further sub-analyzed by type of abnormality A-single-whole-chromosome, S-segmental, C-complex (≥2 full-chr-aberrations). Segmental aberrations were divided into subgroups of S + (segmental gain), S-(segmental loss) and CS(complex segmental). Main results and the role of chance: High resolution NGS PGT-A analysis of 17731 embryos showed 54.9% were euploid, 31.5% were aneuploid and 13.6% mosaic. In the oocyte provider's age of ≤ 33 group, significant differences between paternal age group A vs. B, C and D were found in euploidy rates (68.8%, 62.5%, 61.7%, 59.0% respectively; p = 0.00559). There were no significant differences in aneuploidy rates (19.1%, 22.7%, 22.5%, 24.6% respectively; p = 0.07184) or mosaicism rates (12.1%, 14.8%, 15.8%, 16.3%; respectively, p = 0.23754). In the oocyte provider's age of ≥ 34 group, decreasing euploidy rates and increasing aneuploidy rates were observed between all paternal age groups (p = 0.00001 and p < 0.00001, respectively), and no significant differences in mosaicism rates (14%, 12%, 10.2%, 11.6% respectively) reflecting the maternal age effect on euploidy/aneuploidy. In the oocyte provider's age of ≤ 33 group, paternal group A (2.3%) had significantly lower segmental (S) rates compared to groups B (4.3%, p = 0.027599), C (3.3%, p = 0.039924) and D (4.6%, p = 0.018478). In addition, segmental losses (S-) were lower in group A (1.3%) compared to groups B (3.4%, p = 0.020431), C (3.1%, p = 0.043166) and D (3.7%, p = 0.016385). Limitations, reasons for caution: The main limitation was the retrospective nature of this study; however, multiple regression analyses were conducted to limit potential bias by adjusting for sperm and oocyte characteristics. In addition, PGT-A analysis cannot provide information on origin of the aneuploidy and all conclusions are deduced from indirect associations to paternal age. Wider implications of the findings: The results of this study provide important information to assist fertility practitioners when providing pre-conception counseling to patients, particularly for couples in which the male partner belongs to an older age group. Trial registration number: na